E-module Characteristics of the Sensory System and Students' Perception of E-modules in Grade XI SMA Trisakti Medan - Johana Intan Leonora; Adisti Ratnapuri; Fajar Adinugraha (Universitas Tidar, 2021)
This study aims to develop an electronic module for the material of sensory system which is continued by investigating students' perceptions toward the E-module that is made. This research method is Research and Development (R&D). This research is only up to the design revision stage, not going to the mass production. This research is conducted at SMA Trisakti, Medan from March to July 2021. Previously, E-module is validated by language, material, and media validators which are classified as very suitable to be used as learning media at school. The E-module of sensory system contains cover, introduction, concept maps, book characteristics, material description, videos for learning, articles, questions for exercise with the answer keys, and bibliography. The material description will be divided into five parts. There are the eyes, nose, ears, tongue, and skin. In the E-module, it is also linked to video that can make it easier for students to understand the material. The E-module of sensory system belongs to a good category rating and interests the eleventh graders of SMA Trisakti Medan.